Integrating production functions of timber, forage, and cattle to achieve sustainable resource management. - Bondaroff, Jonathan T. (Author); Hawkins, Chris (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2010)
In the Peace Forest District (PFD) of British Columbia (BC), Canada, approximately 40 percent of forest tenures contain overlapping licenses to graze under the Range Act on Crown range in broadleaf and mixedwood forest types. Resource conflict, over land usage, will increase because of more utilization of broadleaf and mixedwood stands in the PFD. Aspen (Populus tremuloides Michx.] harvesting and reforestation appears to have the greatest impact on forage availability to domestic livestock areas through significant reductions in cattle access as a result of aspen regeneration. Geographical Information System (GIS) analysis and ground-truthing were done on three PFD community pastures. Two areas were surveyed during the 2002 - 2005 grazing seasons while the third was surveyed in 2004 and 2005. For the sites monitored over four years the cattle spent about 60 percent of their time in the same habitat types concurrently including roadways, tame pasture, and mature 'park-like' aspen stands. This exacerbates potential conflict between the cattle, forest industries, and other resource development industries such as oil and gas development. --P.ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1647062